A Versatile Method for Cell-Specific Profiling of Translated mRNAs in Drosophila. - Thomas, A.; Lee, P.J.; Dalton, J.E.; Nomie, K.J.; Stoica, L.; Costa-Mattioli, M.; Chang, P.; Nuzhdin, S.; Arbeitman, M.N.; Dierick, H.A. (PLoS ONE, 2012)
In Drosophila melanogaster few methods exist to perform rapid cell-type or tissue-specific expression profiling. A translating ribosome affinity purification (TRAP) method to profile actively translated mRNAs has been developed for use in a number of multicellular organisms although it has only been implemented to examine limited sets of cell- or tissue-types in these organisms. We have adapted the TRAP method for use in the versatile GAL4/UAS system of Drosophila allowing profiling of almost any tissue/cell-type with a single genetic cross. We created transgenic strains expressing a GFP-tagged ribosomal protein, RpL10A, under the control of the UAS promoter to perform cell-type specific translatome profiling. The GFP::RpL10A fusion protein incorporates efficiently into ribosomes and polysomes. Polysome affinity purification strongly enriches mRNAs from expected genes in the targeted tissues with sufficient sensitivity to analyze expression in small cell populations. This method can be used to determine the unique translatome profiles in different cell-types under varied physiological, pharmacological and pathological conditions.